Analysis of cerebrospinal fluid tumor-derived DNA to obviate biopsy of IDH-mutant brainstem glioma in an adult - Michael Youssef; Alexandra Larson; Vindhya Udhane; Kala F. Schilter; Qian Nie; Honey V. Reddi (The Journal of Liquid Biopsy)
Adult brainstem gliomas are rare and present unique diagnostic and therapeutic challenges due to their critical location and limited biopsy feasibility. Molecular profiling of tumor-derived DNA (t-DNA) isolated from cerebrospinal fluid (CSF) is emerging as a minimally invasive alternative for characterizing these tumors and guiding targeted therapy. A 34-year-old woman with brainstem glioma was treated with a standard course of radiation and temozolomide (TMZ) and remained stable for several years. After surveillance imaging revealed disease progression and raised suspicion of IDH-mutant disease on MRI spectroscopy, molecular profiling of CSF was ordered. The Belay Summit test, a novel NGS-based liquid biopsy assay for central nervous system (CNS) tumors, identified variants in IDH1 and TP53 as well as loss of CDKN2A/CDKN2B. Based on these findings, the patient received a short course of radiation and was started on the IDH inhibitor vorasidenib. This case demonstrates the use of t-DNA from CSF for molecular profiling of adult brainstem glioma to identify actionable genomic alterations without surgical risk and allow patients to receive targeted therapy without tissue diagnosis.